Health Locus of Control and Neuropsychological Performance in Latinx and Non-Latinx White Persons Living with HIV (PLWH). (30th August 2019) - Aghvinian, M; Morris, E; Summers, A; Crook, C; Gonzalez, J; Byrd, D; Rivera Mindt, M
Abstract: Objective: Health locus of control (HLOC) refers to health attributions related to one's actions, chance, doctors, or powerful others and impacts health service utilization. Locus of control (LOC) relates to better neurocognitive (NC) function in healthy adults, medication adherence, and quality of life in persons living with HIV (PLWH). No studies have examined HLOC and NC function in PLWH. This study examined how HLOC contributes to NC function in PLWH. Participants and Method: This cross-sectional study included 130 PLWH (Latinx: n = 95; non-Latinx White [NLW]: n = 35) who completed an NC battery and Multidimensional Health Locus of Control Scale Form C (MHLS-C). MHLS-C has 4 subscales (internal, chance, doctors, and powerful others; 1 = Strongly Disagree – 6 = Strongly Agree). Demographically corrected NC T-scores were used for average global NC and domain T-scores. Results: The Latinx group did worse than the NLW group in global NC, learning, memory, and verbal function (ps < .05). In the Latinx group, MHLS-C Chance negatively related to global NC, learning, memory, and fluency (ps < .05); Powerful Others was negatively related to global NC, learning, and memory (ps < .05). In the NLW group, MHLS-C Chance negatively related to learning and memory (ps < .05). In hierarchical regressions, our model (Step 1: ethnicity and Step 2: MHLC Chance and Powerful Others subscales) predicted global NC (R^2 = .10), learning (R^2 = .30), and memory (R^2=.27; all ps < .05), such that ethnicity was not significant (all ps > .05). Additionally, greater MHLS-C Chance predicted worse NC function (β's = -.22 to -.40, ps < .05). Conclusions: Chance HLOC is related to worse NC function in Latinx and NLW groups, but more strongly in the Latinx group. Ethnicity no longer predicted NC function once chance HLOC was considered. These findings align with prior research in the Latinx population about "fatalismo, " a belief that life events are predestined, and highlight the importance of health professionals addressing perceptions of control over one's health to improve outcomes, including NC functioning.